The effect of phosphatidylserine-containing omega-3 fatty acids on memory abilities in subjects with subjective memory complaints: a pilot study - Yael Richter (Dove Medical Press, 2010)
Yael Richter1, Yael Herzog1, Tzafra Cohen1, Yael Steinhart21Enzymotec LTD, Migdal-HaEmeq, Israel; 2Department of Marketing, Haifa Graduate School of Management, University of Haifa, IsraelObjective: To evaluate for the first time the efficacy of safe-sourced phosphatidylserine-containing omega-3 long chain polyunsaturated fatty acid (PS-omega-3) in improving memory abilities.Methods: PS-omega-3 was administered daily for 6 weeks to eight elderly volunteers with subjective memory complaints. The Cognitive Drug Research test battery was used to assess the effect on their cognitive abilities.Results: PS-omega-3 supplementation resulted in 42% increase in the ability to recall words in the delayed condition.Conclusion: PS-omega-3 may have a favorable effect on memory in subjects with subjective memory complaints. PS-omega-3 may serve as a safe alternative to phosphatidylserine extracted from bovine cortex.Keywords: cognitive, memory, omega-3, phosphatidylserine